2011
DOI: 10.5173/ceju.2011.03.art19
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORTS Retroperitoneoscopic ureterocutaneostomy as a method of urinary diversion in case of complicated urinary fistula after radiotherapy

Abstract: The case of 71-year-old woman with massive vesicovaginal and recto-vaginal fistula after radiotherapy treated with bilateral laparoscopic ureterocutaneostomy is presented. A retroperitoneoscopic access was applied. The technical aspects of the procedure are described. The interdisciplinary character of this not so rare problem is underlined. In our opinion this kind of procedure may be considered as a valuable alternative for commonly used methods of urine deviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As the technology of ostomy pouches becomes more advanced, the compatibility of ostomy pouches with tissue is also improving, and the occurrence of skin irritation becomes increasingly less common and adverse effects are also becoming less frequent ( 15 ). The improved tubeless cutaneous ureterostomy procedure evaluated in this study had the following features ( 16 ): i) during ureter isolation, tissues on the periphery of the ureter were retained as much as possible to avoid damaging the supply vessels of the ureter; ii) ureter isolation spanned approximately 10 cm from the abdominal wall stoma, and the anastomotic stoma was enlarged; iii) the external coat of the ureter on the abdominal skin stoma side was fixed onto the abdominal wall to avoid placing excessive tension on the ureter; iv) a total of 2 single J tube stents were left in the ureter to avoid anastomotic stoma stenosis and urine leakage. The results of this study showed that the incidence of complications of the ‘improved’ group was significantly lower than that of other 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…As the technology of ostomy pouches becomes more advanced, the compatibility of ostomy pouches with tissue is also improving, and the occurrence of skin irritation becomes increasingly less common and adverse effects are also becoming less frequent ( 15 ). The improved tubeless cutaneous ureterostomy procedure evaluated in this study had the following features ( 16 ): i) during ureter isolation, tissues on the periphery of the ureter were retained as much as possible to avoid damaging the supply vessels of the ureter; ii) ureter isolation spanned approximately 10 cm from the abdominal wall stoma, and the anastomotic stoma was enlarged; iii) the external coat of the ureter on the abdominal skin stoma side was fixed onto the abdominal wall to avoid placing excessive tension on the ureter; iv) a total of 2 single J tube stents were left in the ureter to avoid anastomotic stoma stenosis and urine leakage. The results of this study showed that the incidence of complications of the ‘improved’ group was significantly lower than that of other 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures are unsuccessful when URF occurs multiple times and increases the morbidity and mortality in patients [ 10 ]. Recurrent URF may require patients to be subjected to permanent urinary and fecal diversion [ 17 ]. Many authors have suggested that there is no ideal method of repair because of the rare occurrence of URF and the fact that a randomized clinical trial comparing the various methods has yet to be completed.…”
Section: Discussionmentioning
confidence: 99%